Sumerian "Firsts" (The Biblical archaeology review, 1984)
For thousands of years, the Sumerians were a forgotten people. No book recorded their achievements; no spade unearthed their treasures. The Sumerians had passed out of history, until, in the mid-19th century, linguists studying Assyrian cuneiform writing discovered cuneiform tablets written in another language. Linguists and archaeologists alike soon began to realize that in […]